ANALISIS PENGARUH BOOK VALUE, ECONOMIC VALUE ADDED, DAN INTELLECTUAL CAPITAL TERHADAP MARKET VALUE PERUSAHAAN (STUDI PADA EMITEN NON PERBANKAN DALAM INDEKS LQ-45) - Wibowo Wibowo; Mailani Mailani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2010)
This research aims to know the effect of book value, economic value added and intellectual capital on the maket value offirms. This research added variables of book value, EVA, and intellectual capital same as Huang & Wang (2008) had been done in their research. Purposive sampling method was used in taking research samples, and the periods of this research were from 2005 to 2008. 101 non banking firms in LQ-45 indexes from 2005 to 2008 were used as samples in this research. The results of this research showed that book value has significant influence on the market value offirms. EVA has significant influence on market value in first model of this research but it becomes no significant influence on market value of firm in second model of this research after adding intellectual capital. Moreover, this research also found that intellectual capital provides incremental information for the evaluation of stocks (market value).